1975
DOI: 10.1002/cpt1975172159
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide binding to human albumin and plasma of nephrotic children

Abstract: The extent and nature of furosemide (F) binding to human albumin (HA) and to the plasma of 6 children with nephrotic syndrome were studied by equilibrium dialysis at 37 degrees C and pH 7.4 with 14C-F. At a total concentration of 3.4 mug/ml (therapeutic range), the unbound fraction of F to 4 gm per 100 ml HA was 2.79 plus or minus 0.35. The degree of binding was relatively constant from 1.8 to 36 mug/ml of F concentration. The percentage of unbound F doubled when total concentration of the drug was increased m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
45
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(52 citation statements)
references
References 3 publications
7
45
0
Order By: Relevance
“…This was probably due to the presence of endogenous and exogenous (drugs) substances which compete with furosemide for binding sites on the plasma proteins. Since furosemide is exclusively bound to albumin (7,10), the presence of hypoalbuminemia has been postulated (11) as a possible cause for reduced drug binding of furosemide in patients with renal dysfunction. However, the kidney transplant patients in this study were normal with respect to serum albumin levels, and no significant correlation was observed between percent free of furosemide and albumin concentration (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was probably due to the presence of endogenous and exogenous (drugs) substances which compete with furosemide for binding sites on the plasma proteins. Since furosemide is exclusively bound to albumin (7,10), the presence of hypoalbuminemia has been postulated (11) as a possible cause for reduced drug binding of furosemide in patients with renal dysfunction. However, the kidney transplant patients in this study were normal with respect to serum albumin levels, and no significant correlation was observed between percent free of furosemide and albumin concentration (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is highly bound to plasma proteins (6)(7)(8)(9)(10)(11)(12) and gains access to its site of action in the kidney lumen primarily through active secretion via the nonspecific organic acid secretory pathway (13)(14)(15). Previous studies have shown that renal disease can effect dramatic changes in the pharmacokinetics of furosemide (6,11,(16)(17)(18)(19)(20), including impaired plasma protein binding in uremics (7,11), nephrotics (10,11), and anephric patients (6). The degree of binding of furosemide to plasma proteins in kidney transplant patients has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Furosemide is a highly protein-bound (>98%), weak organic acid which is actively secreted into the urine by organic acid transporters (OATs) in the proximal tubules (24,25). In patients with elevated plasma urea and creatinine concentrations, uremic acids may theoretically alter furosemide PK by competing for tubular secretion by OATs (26).…”
Section: Discussionmentioning
confidence: 99%
“…The dialysis chambers (Cellusep; Spectrum) have a volume of 250 l and are separated by a membrane measuring 1 cm 2 . Serum samples were dialyzed against the same volume of red blood cell buffer (20) placed in the second compartment. The chamber was then placed in a rotator (Dianorm, Munich, Germany), and dialysis was carried out at 16 rpm at 37°C for 24 h. Following incubation, aliquots of both compartments were counted, and the free fraction was calculated.…”
Section: Methodsmentioning
confidence: 99%